Antibiotic tolerance in environmentally stressed Bacillus subtilis: physical barriers and induction of a viable but non-culturable state. Issue 1 (29th June 2022) - Morawska, Luiza P; Kuipers, Oscar P
Abstract: Bacterial communities exposed to rapid changes in their habitat encounter different forms of stress. Fluctuating conditions of the microenvironment drive microorganisms to develop several stress responses to sustain growth and division, like altering gene expression and changing the cell's physiology. It is commonly known that these protection systems may give rise to differently adapted subpopulations and indirectly impact bacterial susceptibility to antimicrobials. This study focuses on the adaptation of a soil-dwelling bacterium, Bacillus subtilis, to sudden osmotic changes, including transient and sustained osmotic upshift. Here, we demonstrate that physiological changes caused by pre-exposure to osmotic stress facilitate B. subtilis ' entry into a quiescent state, helping them survive when exposed to a lethal antibiotic concentration. We show that the adaptation to transient osmotic upshift with 0.6 M NaCl causes decreased metabolic rates and lowered antibiotic-mediated ROS production when cells were exposed to the aminoglycoside antibiotic kanamycin. Using a microfluidic platform combined with time-lapse microscopy, we followed the uptake of fluorescently-labelled kanamycin and examined the metabolic activity of differently preadapted populations at a single-cell level. The microfluidics data revealed that under the conditions tested, B. subtilis escapes from the bactericidal activity of kanamycin by entering into a non-growing dormant state. Combining single-cell studies and population-wide analysis of differently preadapted cultures, we demonstrate that kanamycin-tolerant B. subtilis cells are entrapped in a viable but non-culturable (VBNC) state.